New upper bounds on the maximal size of an arc in a projective Hjelmslev plane - Honold, Thomas; Kiermaier, Michael; Landjev, Ivan (2020 Algebraic and Combinatorial Coding Theory (ACCT), 2020)
In this paper we present new upper bounds on the size of an arc in the projective Hjelslev planes PHG(2, R), where R is a chain ring of mutilicity index 2.